Design, Preparation, and Bioactivity Study of New Fusion Protein HB-NC4 in the Treatment of Osteoarthritis - Wang, Yaya; Li, Lian; Wei, Qiang; Chai, Rongrong; Yao, Qingqiang; Liang, Chen; Wang, Fuwen; Li, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
Osteoarthritis (OA) is now becoming the main disease that affects public health. There is no specific medicine used for OA in clinical until now. Recently, several studies demonstrated that OA is closely related to the complement system, and some complement regulators such as N-terminal non-collagenous domain 4 (NC4) aimed at alleviating OA have shown a promising therapeutic effect. However, targeting ability is the main limitation for NC4. In this study, a fusion protein named heparin-binding domain-N-terminal non-collagenous domain 4 (HB-NC4) was proposed to solve this problem, which could provide a better way for OA treatment. First, HB-NC4 plasmid was constructed using ClonExpress II one-step ligation kit method. And Escherichia coli BL21 was utilized to express the fusion protein, Ni2+-Sepharose, and a desalting gravity column were introduced to purify HB-NC4. The results showed that 0.84 mg HB-NC4 could be obtained from 1 L culture medium with a purity higher than 92.6%. Then, the hemolytic assay was introduced to validate the anti-complement activity of HB-NC4, these results demonstrated that both HB-NC4 and NC4 had a similar anti-complement activity, which indicated that heparin-binding (HB) did not affect the NC4 structure. Targeting ability was investigated in vivo. HB-NC4 showed a higher affinity to cartilage tissue than NC4, which could prolong the retention time in cartilage. Finally, the destabilization of the medial meniscus (DMM) model was applied to investigate HB-NC4 pharmacodynamics in vivo. The results indicated that HB-NC4 significantly slowed cartilage degradation during the OA process. In summary, compared with NC4, HB-NC4 had better targeting ability which could improve its therapeutic effect and prolonged its action time. It could be used as a new complement regulator for the treatment of OA in the future.